Comparison of Contemporary and Historic Highly Pathogenic Avian Influenza A(H5N1) Virus Replication in Human Lung Organoids - Meaghan Flagg; Brandi N. Williamson; Johan A. Ortiz-Morales; Tessa R. Lutterman; Emmie de Wit (Emerging Infectious Diseases)
We compared virus replication and host responses in human alveolar epithelium infected with highly pathogenic avian influenza (HPAI) A(H5N1) viruses. A/Vietnam/1203/2004 replicated most efficiently, followed by A/Texas/37/2024, then A/bovine/Ohio/B24OSU-342/2024. Induction of interferon-stimulated genes was lower with A/Texas/37/2024 and A/bovine/Ohio/B24OSU-342/2024, which may indicate a reduced disease severity of those viruses.